Strategy for application of macro-, micronutrients and liming in acid lateritic soils of Jharkhand for sustainable growth of Flemingia semialata - GHOSAL, S; MEENA, S C; GHOSH, J; THAMILARASI, K (The Indian Journal of Agricultural Sciences, 2016)
An experiment was carried out during 2011-12 to 2013-14 at the Institute Research Farm, Ranchi (23o23’N longitude, 85o23’ E latitude and 650 m above MSL) to study the effects of different primary nutrients, liming and micronutrients (boron, molybdenum, zinc and copper) on the growth of 5 year old established plantation of semialata (Flemingia semialata) and residual effect on soil fertility. The experiment consisted of 12 treatments. These included recommended doses of zinc, copper, boron, molybdenum, liming @ 125 g/m2, two doses of potassium (30 and 60 g/ plant), two doses of nitrogen (25 and 50 g/plant), combination of N-P-K (50, 25 and 50 g/ plant) and two control treatments (lac inoculated and lac un-inoculated) replicated thrice and was conducted in Randomized Block Design. Effect of year was separated by analyzing variance due to years adopting factorial mode. Treatments like liming, nitrogen application (50 g) and NPK combination (50-25-30 g) excelled by producing 1.47, 1.42 and 1.48 kg fresh biomass/plant as against 1.23 kg in control (inoculated). Boron, zinc, potassium and copper application occupied a position in the middle order (1.28 to 1.36 kg). Plant mortality significantly went down to merely 5% on third year as against 30% in first year. It indicated that cumulative effect of imposition of treatment in present rate on the experimental plot has benefited the plant stand significantly. Copper level increased to 3 ppm in copper applied treatments which was approximately three times more than that of normal soil. Similarly, zinc content was raised to 2.52 ppm on the plots where zinc was applied. Potassium application at higher rate has increased the soil potassium level 23%, suggests that loss of potassium from this soil is very negligible. Study also revealed that only four parameters varied markedly due to liming. These were CaCO3 content, potassium and manganese level and soil pH. Lower rate of liming (14 lime/ha/year) proved to be efficient and remunerative; it could raise the pH 0.33 unit.